PERAN LAKI-LAKI DALAM KESEHATAN REPRODUKSI DAN PENCEGAHAN KEKERASAN - Sindung Haryanto; Teuku Fahmi (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2015)
The purpose of this study was to determine the differences in the level of participation of men in reproductive health and the prevention of violence between rural areas and urban areas. This study uses a combined approach of quantitative and qualitative approaches was carried out gradually. This research was conducted in two rural communities / villages where each representing urban and rural area types. The number of samples involved in this study of 160 people who overall are male-headed households in the study area. The results showed: (1) related to the output variable (effect), there is a difference between the proportion of the value of a variable, that is, the conclusion of a research aspects (eg on a stand regarding the relationship of men and women) could not be made public, but should be seen each variable; (2) acts of domestic violence is still quite prevalent both in the intervention and non-intervention; (3) on reproductive health-related behaviors / AIDS HIV is generally not significant differences between types of urban and rural regions.